How does authentic leadership boost work engagement? Exploring the mediating role of work meaningfulness and work–family enrichment - Silva, V. H. (2023)
Leadership is crucial in organizational life. Positive leadership is marked by transparent, trust-based leader–follower relationships that significantly boost employees’ dedication and engagement. Work engagement stems from a positive bond between workers, their job, and their organization. Authentic leadership, in particular, has been found to enhance work engagement, but this relationship is quite complex. Prior studies have explored the psychological processes linking organizational context and work-related attitudes and provided intriguing insights, such as that employees consider work to be part of their identity and that positive work experiences enrich family life. This research more closely examined authentic leadership’s impact on work engagement, including the mediating effect of meaningful work and work–family enrichment. A cross-sectional study was conducted with data from various organizations’ employees (number = 292). Multiple regression analyses’ results support the theoretical model, confirming a significant positive link between perceived authentic leadership and work engagement. These variables are directly and indirectly related through the proposed mediators. Implications for human resource management are discussed, especially strategies that increase work environments’ positive impacts on work engagement.